NEW ECO-FRIENDLY ANTI-CORROSION PIGMENTS BASED ON MONTMORILLONITE - Danyliak, M.-O.M.; Korniy, S.A. (Reports of the National Academy of Sciences of Ukraine, 2024)
New eco-friendly anti-corrosion pigments based on montmorillonite enriched with zinc cations were obtained by the liquid phase ion exchange method. It was shown that zinc content in modified montmorillonite increases with increasing concentration of Zn(NO3)2 solution. It has been established that montmorillonite-based pigments enriched with zinc cations increase corrosion resistance of D16T alloy in acid rain environment by electrochemical methods. Zn-montmorillonite obtained by modification with a 0.5 M Zn(NO3)2 solution shows the highest anticorrosion effect. It was found that the degree of protection of aluminum alloy D16T in acid rain environment using Zn-montmorillonite was approximately 90%.